PERENCANAAN STRATEGIS BERBASIS DATA DAN KEUNGGULAN KOMPETITIF DI PERUSAHAAN DIGITAL - M. Fakhriansyah; K.M. Faisal Reza; Elin Destri Mirani (Berajah Journal, 2026)
Digital transformation has driven organizations to adopt a data-driven approach to strategic planning to enhance competitiveness amidst increasingly complex market dynamics. This study aims to analyze the role of data-driven strategic planning in creating competitive advantage in digital companies. The study employed a literature review method by examining various scientific publications, industry reports, and relevant academic articles on the use of data analytics, artificial intelligence, and evidence-based decision-making in the context of digital companies. The study results indicate that data integration in the strategic planning process can improve decision-making accuracy, accelerate organizational response to changes in the business environment, and support more adaptive product and service innovation. In addition, the use of analytical technology enables companies to identify market opportunities, understand customer behavior, and optimize operational efficiency on an ongoing basis. However, the implementation of a data-driven approach still faces several challenges, such as limited data quality, human resource readiness, information security, and the need for effective data governance. This study confirms that data-driven strategic planning is a critical factor in building sustainable competitive advantage for digital companies. The research findings are expected to serve as a conceptual foundation for academics and practitioners in formulating more responsive, innovative, and value-oriented organizational strategies in the digital economy era.